ECONOMIC EQUILIBRIUM AND MONETARY POLICY - V. Krilov (Вестник университета)
The problem of economic equilibrium as a theoretical basis of monetary policy has been considered. It has been noted, that it is necessary to take into account the state of imbalance in the economy and the factors of market failure. The conclusion has been made, that it is important to focus on hybrid forms of monetary policy, which means the use of different combinations of target reference points. The need is implied from this for a more flexible approach to the formation of modern policy of the Bank of Russia, which would not absolutize the regime of inflation targeting.